Small variations in climate and soil conditions may have greater influence on multitaxon species occurrences than past and present human activities in temperate mountain forests. Issue 5 (18th January 2018) - Janssen, Philippe; Fuhr, Marc; Bouget, Christophe
Abstract: Aim: Human activity is known to greatly influence species occurrences. In forest ecosystems, biodiversity is often believed to be influenced by two habitat characteristics: (1) forest continuity, related to a minimum length of time in a wooded state since a threshold date; and (2) stand maturity, related to the availability of late‐developmental‐forest attributes. In a context of ongoing global biodiversity loss, qualifying the effect of past and present human activity on forest ecosystems while taking into account variations in abiotic factors is of primary importance for conservation. Location: Temperate mountain forests in the Northern Alps. Method: Based upon a sampling design crossing forest continuity (ancient vs. Recent) and stand maturity (mature vs. overmature), and while controlling for the effect of two major environmental factors, soil and climate, we explored the individual response of saproxylic beetle, springtail, herbaceous plant and epiphytic macrolichen species to past and present human activity. Results: Forest continuity influenced the occurrence of relatively few species, indicating that past land use had almost no legacy effect on the species occurring in the study forests today. In contrast, stand maturity had an overall positive effect on species occurrences. However, our results showed that species occurrences were more obviously influenced by abiotic conditions. Indeed, beyond the effect of continuity and maturity factors, the probability of presence of numerous species was best explained by climate and soil. Main conclusions: Overall, we show that species occurrence was more influenced by stand maturity than by forest continuity, but also that site‐specific characteristics were of great importance in explaining the probability of presence for numerous species. In the ecological context of alpine forests, these findings emphasize the need to better control for climatic and edaphic conditions in order to (1) improve accuracy in predicting species occurrence and (2) better design areas of conservation interest.